Skeletal anomalies in reared E uropean fish larvae and juveniles. Part 1: normal and anomalous skeletogenic processes - Clara Boglione; Paulo Gavaia; Giorgos Koumoundouros; Enric Gisbert; Mari Moren; Stéphanie Fontagné; Paul Eckhard Witten (Reviews in Aquaculture, 2013)
This critical review summarizes the knowledge about fish skeletal tissues and inherent normal and anomalous development. Particular emphasis is given to existing literature on reared European fishes. The aim was to identify the main gaps of knowledge that require to be filled, in order to precociously identify anomalous developmental patterns that lead to skeletal anomalies in reared finfish larvae and juveniles. The review also aims to extend our knowledge about the factors that are possibly involved in the onset of skeletal anomalies. The final goal is the optimization of the morphological quality of farmed juvenile fish.